1996
DOI: 10.1159/000099773
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Accuracy of Magnetic-Resonance-Guided Gamma Knife Surgery

Abstract: An evaluation of the systematic accuracy of magnetic resonance (MR)-guided Gamma Knife surgery was performed. In two experiments, a cylinder phantom filled with dosimeter gel containing ferrous sulfate was fixed to a stereotactic frame. The gel phantom was irradiated with the Gamma Knife with a single shot using 4-mm collimators. The target point was set at the frame center of the stereotactic system giving coordinate values of X = 100, Y = 100, Z = 100. The maximum target dose was 15 Gy. MR imaging was undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Wu/Lee/Wu/Chu/Guo In one of our previous studies, we found that the systematic accuracy of MRguided Gamma Knife surgery was 0.12 and 0.43 mm in two experiments [13]. The current study demonstrated that the systematic geometrical errors of target delineation between stereotactic MRI and X-ray imaging were within a submillimeter range.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Wu/Lee/Wu/Chu/Guo In one of our previous studies, we found that the systematic accuracy of MRguided Gamma Knife surgery was 0.12 and 0.43 mm in two experiments [13]. The current study demonstrated that the systematic geometrical errors of target delineation between stereotactic MRI and X-ray imaging were within a submillimeter range.…”
Section: Discussionsupporting
confidence: 56%
“…Based on one of the previous studies [13], it is obvious that with the current imaging protocol deviations of x and y coordinates on transaxial MR images were smaller, while the z coordinate has larger deviations. Partial volume effects of slice thickness, in this study being 3 mm, caused the difference.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The MR image clearly demonstrates the contour of the brain tumor in the sellar and juxtasellar region as well as the critical structures, such as optic nerves, optic chiasm, and optic tract, on transaxial, coronal and sagittal images. Although CT scanning has been considered as the gold standard in terms of imaging distortion, modern MR scanners minimize distortion by improvement in homogeneity of the magnetic field [7,8]. In addition, the image is regularly calibrated for linearity of magnetic homogeneity every two weeks in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, several factors contribute to data errors, including imaging distortion, delineation errors in tumor margins, morphology of tumors, computed slices in each tumor, and size of tumors [5][6][7][8] . In this study, we calculated the volume by the Gamma Knife workstation as the basis for determining the data errors from the PACS (product of surface area and thickness of slices) and geometric methods.…”
Section: Introductionmentioning
confidence: 99%